Lack of Ach1 CoA-Transferase Triggers Apoptosis and Decreases Chronological Lifespan in Yeast - Orlandi, Ivan; Casatta, Nadia; Vai, Marina (Frontiers in Oncology, 2012)
ACH1 encodes a mitochondrial enzyme of Saccharomyces cerevisiae endowed with CoA-transferase activity. It catalyzes the CoASH transfer from succinyl-CoA to acetate generating acetyl-CoA. It is known that ACH1 inactivation results in growth defects on media containing acetate as a sole carbon and energy source which are particularly severe at low pH. Here, we show that chronological aging ach1 cells which accumulate a high amount of extracellular acetic acid display a reduced chronological lifespan. The faster drop of cell survival is completely abrogated by alleviating the acid stress either by a calorie restricted regimen that prevents acetic acid production or by transferring chronologically aging mutant cells to water. Moreover, the short-lived phenotype of ach1 cells is accompanied by reactive oxygen species accumulation, severe mitochondrial damage and an early insurgence of apoptosis. A similar pattern of endogenous severe oxidative stress is observed when ach1 cells are cultured using acetic acid as a carbon source under acidic conditions. On the whole, our data provide further evidence of the role of acetic acid as cell-extrinsic mediator of cell death during chronological aging and highlight a primary role of Ach1 enzymatic activity in acetic acid detoxification which is important for mitochondrial functionality.